A new secure and privacy preserved protocol for IEEE802.11s networks. Issue 77 (August 2018) - Abouhogail, Reham Abdellatif; Gadelrab, Mohammed S.
Abstract: In this paper, a fast and efficient handover authentication protocol is proposed. It is considered as a solution to the performance problem of IEEE802.11s Wireless mesh networks (WMNs). Actually, it suffers from long handover delay time, which is unsuitable for the mobility in WMNs. The proposed protocol presents a new and secure method to reduce the handover time based on the ticket authentication. Since Mesh STA User ( MU ) is directly authenticated by the Mesh Access Points ( MPs ), without involving the Authentication Server ( AS ). Furthermore, a new design of the ticket is presented. The security analysis proves the efficiency of the presented protocol against the known types of attacks. A security test is carried out on the proposed protocol using the formal verification tool, AVISPA, which declares that the presented protocol is secure. The performance analysis proves that a significant improvement in computation and communication overhead is achieved. Moreover, the presented scheme satisfies good privacy preservation. A simple network simulation is carried out, which confirms the results of the performance analysis.